Penciptaan Manusia dalam Al-Qur’an dan Ilmu Embriologi: Tafsir Ilmi - Ihyaudin Ihyaudin; Wulan Octaviani Putri; Indah Ramadhani Priyono; Andi Rosa (Jurnal Budi Pekerti Agama Islam, 2025)
The Qur’an contains a wealth of information and regulations regarding the Essence and purpose of the creation of the universe, including the process of human Creation. It describes several stages of human development starting from the prenatal Phase, namely the nutfah (sperm drop), alaqah (a clinging clot), mudghah (a chewed-like Lump of flesh), izam (formation of bones), and khalqan akhar (the formation of a complete Human being). In interpreting these stages, Ar-Razi applies a philosophical approach, while Hamka employs a scientific approach in their interpretations of Surah al-Mu’minun verses 12-14. The main issue explored in this study is how the two exegetes interpret Qur’an Surah al-Mu’minun verses 12-14 concerning the process of human creation. This research Is qualitative, employing a library research approach and a comparative method between Mafatih al-Ghayb and Tafsir al-Azhar. Data collection is conducted through Documentation techniques, which involve gathering relevant written or recorded Documents. The findings conclude that although both scholars present similar theories, They adopt different approaches. Ar-Razi interprets these verses as referring to the creation Of Prophet Adam and his descendants, whereas Hamka interprets them as describing the general process of human creation (the offspring of Adam).